Risiko dan Faktor Produksi Usahatani Padi Sawah Tadah Hujan Kabupaten Pangkajene Kepulauan - Arifin, Arifin; Azisah, Azisah; Sadat, Mohammad Anwar; Pata, Abdul Asis; Megawati, Megawati; Asriyani, Asriyani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
An agricultural business is a business that is always characterized by yield variability or high risk. The implementation of lowland rice farming contains many risks which result in a decrease in production, some of which cannot be controlled. Increasing the production of farmers and farm managers must understand and be able to apply the factors of production properly, otherwise, the increase in production will not be achieved. The purpose of this study was to analyze the production risk of rainfed lowland rice farming and analyze the production factors of rainfed lowland rice farming. This research was conducted in Pacikong Baja Village, Labakkang District, Bonto Kio Village, Minasatene District, and Pangkajene Islands Regency. The research was carried out from October - November 2023. The total research population was 238 people and 25% of the total population was taken as research samples, namely 60 farmers. The sample of farmers was taken using a simple random sampling method. Data collection techniques used are observation/observation, and interviews. The types of data are qualitative and quantitative data. There are two sources of data, namely primary and secondary data. Data analysis used is risk analysis and multiple regression. The results showed that based on the large value of the coefficient of variation, it could be seen that farmers in Pacikong Baja Village and Bonto Kio Village were at risk (CV > 0.50) in carrying out rice farming in rainfed rice fields. The results of production risk in Bonto Kio Village are greater than in Pacikong Baja Village. It can be concluded that rainfed lowland rice farming is categorized as risky in production. Factors that have a real and positive influence on the production of rainfed lowland rice farming are land area, amount of urea fertilizer, amount of pesticides, and farming experience. While the real and negative effect is the number of seeds.